2006
DOI: 10.2337/db05-1535
|View full text |Cite
|
Sign up to set email alerts
|

Common Variants of the Endothelial Nitric Oxide Synthase Gene and the Risk of Coronary Heart Disease Among U.S. Diabetic Men

Abstract: Endothelial nitric oxide synthase (eNOS) gene represents a promising candidate gene for coronary heart disease (CHD) because of its impact on eNOS activity. We systematically examined the associations of eight variants of the eNOS gene (two potentially functional variants [؊786T>C and Glu298Asp] and six tagging single nucleotide polymorphisms) with CHD risk in a large cohort of diabetic patients. Among 861 diabetic men (>97% Caucasian) from the Health Professionals Follow-Up Study, 220 developed CHD, and 641 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1
2

Year Published

2007
2007
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 48 publications
1
16
1
2
Order By: Relevance
“…On the contrary, our results differed from those of Zhang et al (47), who observed no association of Glu 298 Asp polymorphism and CAD risk in diabetic men. To try to reconcile the latter and our present results, it must be considered that in type 2 diabetes mellitus, other risk factors are more prevalent and could mask the influence of NOS3 variants on CAD.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…On the contrary, our results differed from those of Zhang et al (47), who observed no association of Glu 298 Asp polymorphism and CAD risk in diabetic men. To try to reconcile the latter and our present results, it must be considered that in type 2 diabetes mellitus, other risk factors are more prevalent and could mask the influence of NOS3 variants on CAD.…”
contrasting
confidence: 57%
“…The association between several polymorphisms of the NOS3 gene and CAD and restenosis risks has been previously studied (2,5,6,8,25,45). Zhang et al (47) did observe a potential involvement of 786T3 C, Glu 298 Asp, and intron 8 single-nucleotide polymorphism (SNP) variants in the atherogenic process in diabetic subjects with CAD. Other studies showed that homozygosity of Glu 298 Asp and Ϫ786T3 C polymorphisms of the NOS3 gene represented an independent risk factor for in-stent restenosis (12,40), and the 894G3 T polymorphism of NOS3 gene was associated with an increased risk of death and/or myocardial infarction within 1 yr after stent placement (13).…”
mentioning
confidence: 99%
“…87 Glycoxidation and lipid oxidation are thought to contribute to atherosclerosis and, therefore, it may be expected that alleles for genes that protect cells from oxidation damage may retard cardiovascular disease associated with diabetes. Common variants in the paraoxonase 1 gene 88 and the endothelial nitric oxide synthase gene 89 were shown to modulate risk of coronary heart disease among subjects with type 2 diabetes. The important contribution to atherosclerosis of RAGE has been shown in several studies of diabetic and nondiabetic mice.…”
Section: Candidate Genesmentioning
confidence: 99%
“…to our knowledge, this is the first report to determine the association of CAD with three eNOS polymorphisms by comparing four subgroups divided according to both cad and t2dm. Zhang et al (24) examined eNOS variants and the risks of coronary heart disease among diabetic men in the uS and found that the genotype distributions of -786t>c and 894G>t were not significantly different among the men with or without coronary heart disease, but non-diabetic samples were not included in their study. We observed that the allele frequencies of eNOS -786T>C, 4a4b and 894G>T were not significantly different between the non-diabetic cad patients and the non-diabetic controls (Table II).…”
Section: Discussionmentioning
confidence: 99%